From nuclei to neutron stars: simple binding energy computer modelling in the classroom (part 1). (25th February 2021) - Pastore, A; Romero, A M; Diget, C; Rios, A; Leech, K; Stokoe, P
Abstract: We present a simple activity based on the liquid-drop model which allows secondary school students to explore the uses of mathematical models and gain an intuitive understanding of the concept of binding energy, and in particular the significance of positive binding energy. Using spreadsheets provided as supplementary material, students can perform simple manipulations on the different coefficients of the model to understand the role of each of its five terms. Students can use the spreadsheets to determine model parameters by optimising the agreement with real atomic mass data. This activity can be used as the starting point of a discussion about theoretical models, their validation when it comes to describing experimental data and their predictive power towards unexplored regimes.